2011
DOI: 10.1128/aac.01056-10
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antimicrobial Activity of Lysostaphin-Coated Hernia Repair Meshes

Abstract: Bacterial infections by antibiotic-resistant Staphylococcus aureus strains are among the most common postoperative complications in surgical hernia repair with synthetic mesh. Surface coating of medical devices/ implants using antibacterial peptides and enzymes has recently emerged as a potentially effective method for preventing infections. The objective of this study was to evaluate the in vitro antimicrobial activity of hernia repair meshes coated by the antimicrobial enzyme lysostaphin at different initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 28 publications
3
42
0
Order By: Relevance
“…Kokai-Kun et al demonstrated that lysostaphin has the ability to eradicate biofilm-protected S. aureus from surfaces in vitro [22]. Satishkumar et al examined antimicrobial properties of lysostaphin bound to mesh in vitro, reporting that such enzyme leaching surfaces actively resist bacterial adhesion and prevent subsequent colonization of hernia meshes [23]. Schaffner et al used lysostaphin intravenously in mice challenged with a S. aureus inoculum, showing that the lysostaphin recipients had a significantly higher survival than animals treated with oxacillin or the untreated controls [24].…”
Section: Introductionmentioning
confidence: 96%
“…Kokai-Kun et al demonstrated that lysostaphin has the ability to eradicate biofilm-protected S. aureus from surfaces in vitro [22]. Satishkumar et al examined antimicrobial properties of lysostaphin bound to mesh in vitro, reporting that such enzyme leaching surfaces actively resist bacterial adhesion and prevent subsequent colonization of hernia meshes [23]. Schaffner et al used lysostaphin intravenously in mice challenged with a S. aureus inoculum, showing that the lysostaphin recipients had a significantly higher survival than animals treated with oxacillin or the untreated controls [24].…”
Section: Introductionmentioning
confidence: 96%
“…Other studies monitoring the antibacterial activity of solids with silver or other antibiotics have recorded a wide range of antibacterial efficacies, from 1 log-unit reduction for 24 h exposure [15] to 3 log-units reduction for 5 h exposure [30] and 2 log-units reduction for 30 min exposure.…”
Section: Antibacterial Propertiesmentioning
confidence: 98%
“…Lysostaphin has been extensively studied as a therapeutic agent, with either topical or systemic administration, for the treatment of S. aureus infections (8)(9)(10)(11)(12)(13). Now, recombinant lysostaphin is being effectively developed as a new topical antibacterial agent to control S. aureus infections in burn wounds in China (phase III clinical trials).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro and in vivo studies have shown that lysostaphin is an effective therapeutic agent against antibiotic-resistant S. aureus (8)(9)(10)(11)(12)(13)(14). For example, lysostaphin, given as a single dose (100 mg/kg) or twice daily (30 mg/kg) for 3 days, has been shown to be more effective than vancomycin (30 mg/kg, twice daily for 3 days) for the treatment of experimental aortic valve endocarditis caused by vancomycin-intermediate S. aureus in rabbits (15).…”
mentioning
confidence: 99%